An assessment of the physicochemical and microbiological stability of bottled natural medicinal waters from Polish health resorts - Bartosik, Marta; Szynal, Tomasz; Mazańska, Małgorzata; Matuszewska, Renata; Mąka, Lukasz; Solecka, Jolanta (Geology, Geophysics and Environment, 2025)
Balneotherapy, utilising natural medicinal waters, gases, and peloids, is a clinically effective method for complementing the treatment of various medical conditions. One specific type of balneotherapy is crenotherapy, which involves the oral administration of natural medicinal waters. This study aimed to assess the impact of storage time on the stability of the chemical composition and microbiological quality of bottled natural medicinal waters, as well as to assess the feasibility of using packaged natural medicinal waters at home to prolong the effect post-sanatorium treatment, as recommended by the chief physician responsible for health resorts. Fourteen bottled medicinal waters sourced from seven Polish health resorts were analysed. The study examined the following samples: one HCO3-Cl-Na-Ca, four HCO3-Cl-Na, one HCO3-Mg-Na-Ca, two HCO3-Na-Ca, two HCO3-Ca, two HCO3-Na and two Cl-Na waters. Physicochemical and microbiological parameters were measured at the following times: t0 (immediately after packaging), t1 (midway through the declared shelf life) and t2 (at the end of the shelf life). Physicochemical analysis of the medicinal waters demonstrated the stability of the chemical composition in terms of basic minerals and physicochemical parameters over the product’s shelf life, as defined by the manufacturer. Faecal indicator bacteria or Pseudomonas aeruginosa were absent in all of the samples tested. However, coliform bacteria, potentially of biofilm origin, were detected in one sample. An initially high number of microorganisms, determined at 22°C, observed in three water samples, was no longer detected at the final testing stage. The findings indicate that the medicinal waters analysed maintain stability in chemical composition, organoleptic parameters and microbiological purity throughout the manufacturer’s specified shelf life.